Irrenunciabilidad de los derechos de los trabajadores en relación a la suscripción e impugnación de a las actas de finiquito - Borja Centeno, Erika Rocío (2018)
The Labor Law is based on the permanent experience among the subjects that are part of an employment relationship, being these workers and employers who are immersed in that employment relationship. For many years now, Ecuadorian labor legislation has been understood without even noticing the real situation of the environment in which it is lived, the labor regime has suffered a series of changes that have affected directly or indirectly to the only force that can lead to the development of peoples, the worker. The current Constitution of the Republic of Ecuador guarantees people the right to work, recognizes all forms of work, in relation to dependence, or autonomous and as productive social actors, to workers; labor rights are inalienable, these rights are obtained by the worker because they are dependent on the employer, since these rights are acquired and maintained while the employment relationship exists and upon termination, the worker must receive all the benefits that correspond to the law. and that are established in the Labor Code. The employment contract is the legal economic link through which a person called worker is obliged to provide personal services or to execute a work to another person called employer, personally or under dependency in exchange for remuneration, the employment relationship takes effect from the moment in which the worker executes the work that pacts with the employer; while there is an employment relationship, the worker and the employer will be in harmony and both parties will carry out the stipulations of the work contract, but either suspension or termination of the contract begins the figure known as labor termination, document in which the parties they record the termination of the employment relationship and the benefits that are paid to the worker At that time there are often disputes between employer and employee when they are not canceled benefits that by law correspond to the worker, this is where the subject of study of research work begins because the working class to ignore their rights, are violated the same, that is, there is a violation of rights, although the legal norms that are in force protect and guarantee them; then appear the principle of tutelaridad and irrenunciabilidad of the rights of the workers which force the employer to the fulfillment of the same. Reason for which the present investigation work that has been realized under the modality of study of case, is a thematic one that looks for to demonstrate what is the opportune procedural moment so that the worker can make the impugnation of the act of settlement; although this document has been signed by the worker in front of the Labor Inspector, so that the worker perceives what by law corresponds to him, and since Ecuador is a State of Rights and Justice, those inalienable rights can be acted upon